Customer Loyalty: the influence of company image, service quality, and customer satisfaction as mediators - Safirda, Dea Astry; Salim, Muhartini (Universitas Wiralodra, 2024)
This study aims to determine the effect of company image and service quality on customer loyalty through customer satisfaction at PT PLN (Persero) ULP Teluk Segara. This research methodology uses a questionnaire as a data collection tool obtained from PT PLN (Persero) ULP Teluk Segara. The sampling method uses a non-probability strategy technique with a sample of 120 respondents who use company services at PT PLN (Persero) ULP Teluk Segara. The analysis used is the Structural Equation Model (SEM), which is processed using SmartPLS. The results of the analysis show: 1) Company image has a significant effect on customer satisfaction; 2) Service quality has a significant effect on customer satisfaction; 3) Customer satisfaction has a significant effect on customer loyalty; 4) Company image has a significant effect on customer loyalty; 5) Service quality has a significant effect on customer loyalty; 6) Company image has a significant effect through customer satisfaction on customer loyalty; 7) Service quality has a significant effect through customer satisfaction on customer loyalty. With the findings of this study, it is hoped that the PT PLN (Persero) Teluk Segara ULP company can focus more on improving its image and service quality to increase customer satisfaction, which will ultimately support higher customer loyalty.